PENGARUH KOMPETENSI SOSIAL DAN DISIPLIN KERJA TERHADAP KINERJA GURU DI SMA NEGERI 7 MUARO JAMBI - Lili Andriani, Ferni Irawani Zenita, (SJEE (Scientific Journals of Economic Education), 2017)
This study aims to determine the description of social competence, work discipline and performance of teachers and the influence of social competence and work discipline on the performance of teachers in SMA Negeri 7 Muaro Jambi. The results showed that the picture of social competence has a value of 84.14%, work discipline has a value of 66.27% and teacher performance has a value of 61.40%. Meanwhile, the influence of social competence on teacher performance is summarized model R = 0,361 and R Square = 0,168 with ANOVA value, F = 2,628 with α (sig) = 0,004. The amount of influence of work discipline on teacher performance of model summary R = 0,650 and R Square = 0,422, In ANOVA, value F = 26,300 with α (sig) = 0,000. Meanwhile, the magnitude of the influence of social competence and work discipline on the performance of teachers collectively obtained results model summary R = 0.666 and R Square = 0.443, in ANOVA, value F = 13.920 with α (sig) = 0,000.Kata Kunci : Social Competence, Work Discipline, Teacher Performance